Trading in Federal funds : findings of a three-year survey - Nichols, Dorothy M. (Washington,DC : Federal Reserve System, 1965)
This is the second technical paper on the Federal funds market to be published by the Board of Governors of the Federal Reserve System. It is detailed information on the Federal funds transactions of a larger number of banks over a longer period in order to study the behavior of the market over time.
Bibliographical footnotes.
rua 07/03/17
Loans
Keywords: Banks and banking, Central; Federal funds market (United States); United States of America